2016
DOI: 10.1590/0100-29452016684
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ‘Tuxpan Valencia’ Sweet Orange Grafted Onto 14 Rootstocks in Northern Bahia, Brazil

Abstract: -In the State of Bahia, Brazil, the citrus industry is located on the north coast with the prevalence of the combination 'Pera' sweet orange on 'Rangpur' lime. Scion-rootstock diversification may contribute to the increase of yield and the extension of harvest season, as long as to decrease the risk associated to abiotic and biotic stresses. Therefore, the performance of 'Tuxpan Valencia' sweet orange grafted onto 14 rootstocks was evaluated in Rio Real -BA. Planting was performed in 2006 under rainfed cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 9 publications
5
25
1
3
Order By: Relevance
“…Likewise, Carvalho et al (2016a) carried out a 4-year study and found low cumulative yield of 'Piemonte' mandarin when they were grafted on rootstocks 'Orlando' tangelo, 'Swingle' citrumelo and HTR -051. On the other hand, 'Cravo Santa Cruz Rangpur' lime and 'Sunki Tropical' mandarin induced high cumulative production to 'Valencia Tuxpan' orange in a 5-year study (FRANÇA et al, 2016), whereas the 'Cravo Santa Cruz' lime also impart high production to the 'Piemonte' mandarin (CARVALHO et al, 2016a).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Likewise, Carvalho et al (2016a) carried out a 4-year study and found low cumulative yield of 'Piemonte' mandarin when they were grafted on rootstocks 'Orlando' tangelo, 'Swingle' citrumelo and HTR -051. On the other hand, 'Cravo Santa Cruz Rangpur' lime and 'Sunki Tropical' mandarin induced high cumulative production to 'Valencia Tuxpan' orange in a 5-year study (FRANÇA et al, 2016), whereas the 'Cravo Santa Cruz' lime also impart high production to the 'Piemonte' mandarin (CARVALHO et al, 2016a).…”
Section: Resultsmentioning
confidence: 91%
“…box -1 . França et al (2016) found an interval from 1.8 to 2.5 kg.SS.box -1 in the case of 'Valência Tuxpan' sweet orange grafted on 14 rootstocks in the north of Bahia, whereas Bacar et al (2014) found values that ranged from 1.83 to 1.96 kg.SS.crate -1 in 'Jafa' orange trees grafted on 5 rootstocks in Londrina, Paraná state.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…-survival percentage (%) calculated by the ratio of dead plants to those living up to 2017; -tolerance to field drought estimated during the critical period of drought occurring in September 2017, using a score scale based on visual symptoms of wilting leaves, ranging from grade 1 (no symptoms), grade 2 (slight wilting in up to half of the canopy), grade 3 (slight wilting throughout the canopy) up to grade 4 (intense wilting throughout the canopy and leaf drop), conducted by four evaluators (França et al, 2016).…”
Section: Methodsmentioning
confidence: 99%